Community Empowerment in Tanjungan Village through a Medicinal Plants Showcase for Health Independence - Kartini, Kartini; Setyaningrum, Idfi; Hidayat, Ramdan; Pudjibudojo, Jatie K. (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2025)
Tanjungan Village in Mojokerto Regency has an ecotourism area consisting of a reservoir and a forest, which has not been optimally utilized. The local community also faces limitations in managing their health independently. This community empowerment program aims to enhance health self-sufficiency through the development of a family medicinal plants (TOGA) showcase at Tanjungan Ecotourism. The program involves guidance on designing the layout of the showcase, medicinal plant cultivation techniques, and the implementation of a sprinkler irrigation system to improve water use efficiency. The results indicate a 17% increase in the community’s knowledge and improved skills in planting and maintaining medicinal plants. Additionally, the use of sprinkler irrigation has reduced water consumption by up to 30%, significantly enhancing plant growth. In addition to providing health benefits, the presence of the TOGA showcase also has the potential to boost the village’s tourism appeal. Therefore, the sustainability of this program needs to be maintained through the optimization of medicinal plant utilization and further assistance in post-harvest processing.